Film properties of plastics and elastomers : a guide to non-wovens in packaging applications - Massey, Liesl K. (Plastics Design Library/William Andrew Pub., 2004)
This extensively revised and updated second edition of the only data handbook available on the engineering properties of commercial polymeric films details many physical, mechanical, optical, electrical, and permeation properties within the context of specific test parameters, providing a ready reference for comparing materials in the same family as well as materials in different families. Data are presented on the characteristics of 47 major plastic and elastomer packaging materials. New to this edition, the resin chapters each contain textual summary information including category, general description, processing methods, applications, and other facts as appropriate, such as reliability, weatherability, and regulatory approval considerations for use in food and medical packaging. Extensive references are provided. The resin chapter material supplier trade name product data are presented in graphical and tabular format, with results normalized to SI units, retaining the familiar format of the 1st edition and allowing easy comparison between materials and test conditions.
Keywords: Plastics.; Elastomers.; elektronické knihy; electronic books